Treatment of kidney stone in a kidney autotransplanted patient with mini-percutaneous nephrolithotomy - Can, Truong Van; Thang, Hoang Vuong; Thanh, Cao Xuan; Tuan, Nguyen Kim; Anh, Nguyen Van Quoc; Viet, Phan Huu Quoc; Hung, Pham Ngoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
We report a case of a 7-year-old child with urolithiasis in autotransplanted kidney treated with minipercutaneous nephrolithotomy. The patient presented with hematuria and graft hydronephrosis. Diagnostic procedures revealed ureterolithiasis as a cause of obstruction and blood in urine. Mini-percutaneous nephrolithotomy was successfully performed and during surgery, all stone fragments were removed. Keywords: Urolithiasis, percutaneous, nephrolithotomy.